Die Ordnung des Theaters. Eine Soziologie der Regie - Hänzi, Denis (Theater, 2013)
Theater direction is today more unfettered, the sphere of artistic possibilities more open, than ever before. Creative chaos on all sides? Not really. Denis Hänzi investigates how old ideals and new realities in the German-language theatrical landscape are deriving from the interplay between individual working methods and institutional configurations. Extrapolating on Bourdieu's concept of habitus/field, he develops a theory of charisma which provides an innovative approach to the analysis of contemporary artistic worlds. That the »order of the theater« bears visible traits of a culture of success which appears to consolidate the male dominance in directing is just one of the illuminating findings that makes this book fascinating for theater-makers and theater-goers alike.